Nanoscale precipitation patterns in carbon–nickel nanocomposite thin films: Period and tilt control via ion energy and deposition angle - Abrasonis, G.; Oates, T.; Kovács, G.; Grenzer, J.; Persson, P.; Heinig, K.; Martinavicius, A.; Jeutter, N.; Baehtz, C.; Tucker, Mark; Bilek, M.; Möller, W. (American Institute of Physics, 2010)
Periodic precipitation patterns in C:Ni nanocomposites grown by energetic ion codeposition areinvestigated. Films were grown at room temperature by ionized physical vapor deposition using apulsed filtered cathodic vacuum arc. We reveal the role of the film composition, ion energy andincidence angle on the film morphology using transmission electron microscopy and grazingincidence small angle x-ray scattering. Under these growth conditions, phase separation occurs in athin surface layer which has a high atomic mobility due to energetic ion impacts. This layer is anadvancing reaction front, which switches to an oscillatory mode, producing periodic precipitationpatterns. Our results show that the ion induced atomic mobility is not random, as it would be in thecase of thermal diffusion but conserves to a large extent the initial direction of the incoming ions.This results in a tilted pattern under oblique ion incidence. A dependence of the nanopatternperiodicity and tilt on the growth parameters is established and pattern morphology control via ionvelocity is demonstrated.